Active material and method for producing same
By forming a thin and dense covering part on the core surface of the lithium manganese oxide battery, including elements such as Ti, Zr, Ta, Nb or Al, and oxygen elements, the problems of manganese element dissolution and interface resistance are solved, and the performance of the battery is improved. stability.
Patent Information
- Application Number
- CN202411346669.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2021-06-10
- Filing Date
- 2022-04-11
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art is difficult to effectively inhibit the dissolution of manganese elements and the interface resistance of solid electrolytes in lithium manganese oxide batteries, resulting in a degradation of battery performance.
A thin and dense covering part is formed on the core surface of the lithium manganese oxide, including elements such as Ti, Zr, Ta, Nb, or Al, and oxygen elements. The covering part is formed by atomic layer deposition method to ensure the average thickness and specific surface area of the covering part. The ratio is within the range of 0-15 mass %/(cm3/g), which prevents the dissolution of manganese elements and the interface resistance.
Effectively inhibit the dissolution of manganese elements, reduce interface resistance, improve the rate characteristics and cycle stability of the battery, prevent the core performance from being reduced, and do not weaken the original performance of the core.
Smart Images

Figure BDA0005061157800000181
Abstract
Description
[0001] This application is a divisional application of an application with a filing date of April 11, 2022, application number 202280003892.3, and invention name “Active substance and method for producing the same”. Technical Field
[0002] The present invention relates to active substances and methods for their production. Background Art
[0003] Batteries, which consist of a positive electrode, a negative electrode, and an electrolyte, have high energy density and are easy to reduce in size and weight, and are therefore widely used as power sources for portable electronic devices such as laptop computers and mobile phones.
[0004] As active materials contained in the positive electrode of such a battery, lithium metal composite oxides such as LiCoO2, LiNiO2 and LiMnO2 having a layered crystal structure are known, as well as lithium manganese oxides (LiMn2O4, LiNi 0.5 Mn 1.5 O4) etc.
[0005] In recent years, a technique of forming a coating on the active material has been proposed for the purpose of improving battery performance (for example, see Patent Documents 1 and 2 and Non-Patent Document 1).
[0006] Patent Document 1: JP2005-310744A
[0007] Patent Document 2: WO2014 / 185547A1
[0008] Non-patent document 1: “Surface-Coated LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811)Cathode Materialsby Al2O3, ZrO2, and Li2O-2B2O3 Thin-Layers for Improving the Performance ofLithium Ion Batteries” ORIGINAL RESEARCH published:29November 2019doi:10.3389 / fmats.2019.00309 Summary of the invention
[0009] Active materials having a coating are actively studied as described in Patent Documents 1 and 2 and Non-Patent Document 1. On the other hand, further improvement in the performance of active materials having a coating is desired.
[0010] Therefore, the technical problem of the present invention is to provide an active material capable of obtaining excellent battery performance and a method for producing the same.
[0011] The present invention provides an active material comprising a core portion and a covering portion located on the surface of the core portion.
[0012] The core contains lithium (Li), manganese (Mn) and oxygen (O).
[0013] The covering portion includes an A element (A is at least one selected from the group consisting of Ti, Zr, Ta, Nb and Al) and an oxygen (O) element.
[0014] The average thickness of the coating is T (nm), the specific surface area of the active material is S (nm 2 / g), when the amount of the A element contained in the coating is W (mass %), the value of W / (S×T) is greater than 0 and is 15 mass % / (cm 3 / g) or less.
[0015] Furthermore, the present invention provides an active material comprising a core portion and a coating portion located on a surface of the core portion.
[0016] The core contains lithium (Li), manganese (Mn) and oxygen (O).
[0017] The covering portion includes an A element (A is at least one of Ti, Zr, Ta, Nb and Al) and an oxygen (O) element.
[0018] In a spectrum obtained by line analysis from the surface to the inside of the active material by a STEM method at a cross section of the active material, a half-value width of a peak of the A element in the spectrum is 25 nm or less.
[0019] Furthermore, the present invention provides a method for producing an active material as a preferred method for producing the above-mentioned active material, wherein:
[0020] On the surface of the core containing lithium (Li) element, manganese (Mn) element and oxygen (O) element, a covering part containing A element (A is at least one of Ti, Zr, Ta, Nb and Al) and oxygen (O) element is formed by atomic layer deposition. DETAILED DESCRIPTION
[0021] Hereinafter, the present invention will be described based on the preferred embodiments of the present invention. The active material of the present invention has a core and a covering. The covering is located on the surface of the core. The core and the covering are described below.
[0022] 〔Core〕
[0023] The core portion is a portion that occupies most of the active material and serves as a base material of the active material.
[0024] The core may contain, for example, a lithium metal composite oxide. As the lithium metal composite oxide, a known lithium metal composite oxide may be used. It may be, for example, a lithium-containing composite oxide having a layered rock salt structure represented by the general formula LiMO2 (M represents a metal element), a lithium-containing composite oxide having a spinel structure represented by the general formula LiM2O4, or a lithium-containing composite oxide having an olivine structure represented by the general formula LiMPO4 (M represents a metal element) or LiMSiO4 (M represents a metal element), any one or a combination of two or more thereof. However, it is not limited thereto.
[0025] The core preferably contains a spinel-type composite oxide containing lithium (Li) elements, manganese (Mn) elements, and oxygen (O) elements (hereinafter, the core is sometimes referred to as "core A"). When the active material of the present invention containing core A is used as a positive electrode active material, it has a working potential of 4.5V or more with a metal Li reference potential. "Having a working potential of 4.5V or more with a metal Li reference potential" does not require having a working potential of 4.5V or more only in the form of a platform region, but also includes a case where it has a partial working potential of 4.5V or more. Therefore, the active material of the present invention is not limited to a positive electrode active material consisting only of a 5V-level positive electrode active material having a working potential of 4.5V or more in the form of a platform region. For example, the active material of the present invention may contain a positive electrode active material having a working potential of less than 4.5V in the form of a platform region. Specifically, it is preferred that the 5V-level positive electrode active material accounts for more than 30% by mass, preferably more than 50% by mass, and particularly preferably more than 80% by mass (including 100% by mass) of the positive electrode active material.
[0026] The other elements contained in the core A except for lithium (Li), manganese (Mn) and oxygen (O) may be one or more. When there are two or more other elements, it is preferred that at least one element is one selected from the group consisting of Ni, Co and Fe (hereinafter referred to as "Mn"). 1 element".). 1 The element is a substitution element that mainly contributes to the generation of an operating potential of 3.0 V or more with respect to a metal Li reference potential. Preferably, the other element is one or a combination of two or more selected from the group consisting of Na, Mg, Al, P, K, Ca, Ti, V, Cr, Fe, Co, Cu, Ga, Y, Zr, Nb, Mo, In, Ta, W, Re and Ce. 2 Element. M 2 Elements are substitution elements that mainly contribute to stabilizing the crystal structure and thus improving the properties. 2The element is selected from the above elements, which can improve the capacity retention rate. 1 Elements and M 2 Elements are different kinds of elements.
[0027] As a preferred composition example of the core A, there can be cited a composition containing Li, M 1 Elements and other M 2 Element substitution LiMn2O 4-δ A spinel-type lithium-manganese composite oxide containing a crystal structure obtained by converting a portion of the Mn site in the lithium-manganese complex into a lithium-manganese composite oxide. x (M 1 y M 2 z Mn 2-x-y-z ) 4-δ , Formula (2): General formula [Li x (Ni y M 3 z Mn 3-x-y-z ) 4-δ ] is a spinel-type lithium-manganese composite oxide. As described above, it is preferred that M in formula (2) 3 The element is one or a combination of two or more selected from the group consisting of Na, Mg, Al, P, K, Ca, Ti, V, Cr, Fe, Co, Cu, Ga, Y, Zr, Nb, Mo, In, Ta, W, Re and Ce.
[0028] In formula (1), "x" is preferably 1.00 to 1.20, "y" is 0.20 to 1.20, and "z" is 0.001 to 0.400. In formula (2), "x" is preferably 1.00 to 1.20, "y" is 0.20 to 0.70, and "z" is greater than 0 and 0.5. In addition, "4-δ" indicates that oxygen defects may be contained, and δ is preferably 0 to 0.2.
[0029] Examples of spinel-type composite oxides include lithium manganese oxides such as LiMn2O4 and Li4Mn5O 12 (Li 1.333 Mn 1.667 O4), Li2Mn4O9(Li 0.889 Mn 1.778 O4), LiNi as lithium manganese nickel oxide x Mn 2-x O4 (wherein x represents a number greater than 0 and less than 2), etc.
[0030] It should be noted that other descriptions about the core may be the same as those described in, for example, WO2017 / 150504A1, and therefore are omitted here.
[0031] The core is preferably a particle composed of a lithium nickel metal composite oxide containing Li, Mn and O and having a layered structure (hereinafter, this core is also referred to as "core B"). In addition, the core preferably contains M 4 Elements (where M 4 Represents one or more elements selected from the group consisting of Ni, Co and Al; or one or more elements selected from the group consisting of Ni, Co and Al, and a combination of any one or more elements selected from the group consisting of transition metal elements between Group 3 to Group 11 of the periodic table and typical metal elements from Period 1 to Period 3 of the periodic table. ). The active material of the present invention may contain other components in addition to the core B. In particular, from the perspective of effectively obtaining the characteristics of the core B, the core B is 80% by mass or more, preferably 90% by mass or more, and particularly preferably 95% by mass or more (including 100% by mass).
[0032] Preferably, the core B is represented by formula (3): Li 1+x M 4 1-x Particles consisting of a lithium metal composite oxide having a layered structure represented by O2. In formula (3), "1+x" is preferably 0.95 or more and 1.09 or less.
[0033] It should be noted that other descriptions about the core A and the core B may be the same as those described in, for example, WO2017 / 150504A1 and JP6626434B2, and therefore, they are omitted here.
[0034] 〔Covering part〕
[0035] The covering portion is arranged on the surface of the core portion, covering the surface of the core portion. The covering portion completely covers the surface of the core portion, or partially covers the surface of the core portion in a manner that a portion of the surface of the core portion is exposed. Considering the purpose of the arrangement of the covering portion such as preventing the performance of the core portion from being degraded, it is preferred that the covering portion completely covers the surface of the core portion and the surface of the core portion is not exposed as much as possible.
[0036] The covering portion is arranged on the surface of the core portion for the purpose of preventing the performance of the core portion from being reduced during the use of the battery assembled with the active material of the present invention. In order to achieve this purpose, the core portion is composed of an A element (A is at least one selected from the group consisting of Ti, Zr, Ta, Nb and Al.) and an oxygen (O) element. The covering portion composed of these elements has the effect of effectively preventing the performance of the core portion from being reduced. Among these elements, Zr is particularly preferably used because it can more effectively prevent the performance of the core portion from being reduced.
[0037] Specifically, when a battery having a positive electrode including an active material containing manganese (Mn) is repeatedly charged and discharged, the manganese element constituting the active material tends to be easily dissolved into the electrolyte in an ionic state. If Mn ions are dissolved into the electrolyte, Mn will precipitate at the negative electrode, and as a result, the battery performance may sometimes be reduced. In addition, when the active material is used in a battery including a solid electrolyte, a resistance layer may be formed at the interface between the active material and the solid electrolyte when the battery is charged and discharged. When such a resistance layer is formed, it becomes difficult to smoothly transfer lithium ions, and as a result, the battery performance may be reduced.
[0038] In view of these technical problems, the inventors have repeatedly studied the active material of the covering portion comprising the A element and the oxygen element on the surface of the core comprising the lithium (Li) element, the manganese (Mn) element and the oxygen (O) element. As a result, it is found that the active material with only the covering portion is limited in improving the battery performance. It is believed that one of the reasons is that, since there is an area where the covering portion is not fully formed on the surface of the core, the dissolution of Mn and the reaction with the solid electrolyte cannot be fully suppressed. In addition, it is found that if an attempt is made to fully form a covering portion on the surface of the core, the thickness of the covering portion will increase, and as a result, the covering portion becomes the cause of the increase in resistance, or it will hinder the acceptance of lithium ions.
[0039] Based on the above, the inventors have made intensive research and found that the average thickness of the covering portion is T (nm), the specific surface area of the active material is S (m 2 / g), when the amount of the A element contained in the coating portion is W (mass %), as described later, by providing a value of W / (T×S) greater than 0 and 15 mass % / (cm 3 / g) of active substances, solving the above technical problems.
[0040] Specifically, when the active material of the present invention is used in a battery containing an electrolyte, the manganese contained in the core can be effectively inhibited from dissolving into the electrolyte due to the effect of the covering portion. On the other hand, when the active material of the present invention is used in a solid-state battery containing a solid electrolyte, for example, it is difficult to form a resistance layer at the interface between the active material and the solid electrolyte due to the effect of the covering portion, and lithium ions can be smoothly embedded / de-embedded into the core.
[0041] Thus, no matter whether the active material of the present invention is used in a battery containing a solid electrolyte or a battery containing an electrolyte, the performance degradation of the core can be effectively suppressed by the effect of the covering portion. A preferred method for forming a covering portion having such an advantage will be described later.
[0042] As described above, the covering portion contains at least one A element selected from the group consisting of Ti, Zr, Ta, Nb and Al. The A element may be one or a combination of two or more. Generally speaking, the covering portion may be an oxide of one or more A elements. When the A element is two or more elements, the covering portion may be a composite oxide of two or more elements or an oxide of each element. When the covering portion is an oxide of the A element, the presence ratio of the A element and the oxygen element in the covering portion is preferably a stoichiometric ratio that can form an oxide of the A element.
[0043] In addition to the A element and the oxygen element, the covering portion may further contain a lithium (Li) element. When the covering portion contains the lithium element, the covering portion may be a composite oxide of the lithium element and the A element. When the covering portion is a composite oxide of the lithium element and the A element, the existence ratio of the lithium element, the A element, and the oxygen element in the covering portion is preferably a stoichiometric ratio that can form a composite oxide of the lithium element and the A element.
[0044] It should be noted that the covering portion may contain elements other than the A element, the oxygen element, and the Li element.
[0045] From the perspective of the core part exerting its original performance and effectively preventing the performance of the core part from being reduced, it is preferred that the covering part covers the surface of the core part as thinly as possible and densely. From this perspective, the present inventors have conducted continuous research and found that the average thickness of the covering part is T (nm), the specific surface area of the active material is S (m 2 / g), when the amount of the A element contained in the coating is W (mass %), the value of W / (T×S) is greater than 0 and is 15 mass % / (cm 3 / g) or less is effective. The value of W / (T×S) is an indicator of the covering state of the core part by the covering part. Specifically, it indicates the density of the covering part per 1g of the core part. In the past, although it is known to cover the surface of the particles of the active material to prevent the performance of the active material from being reduced, in the previous technology, the original performance of the active material could not be fully exerted because the covering part was too thick, and the performance reduction of the active material could not be effectively suppressed because the covering part was not dense. In contrast, according to the active material of the present invention, since the covering part covers the surface of the core part thinly and densely, the performance reduction of the core part can be effectively prevented by the covering part without weakening the original performance of the core part.
[0046] From the viewpoint of making the above-mentioned advantageous effects obtained by forming the covering portion more remarkable, the value of W / (S×T) is preferably 0.1 mass % / (cm 3 / g) or more and 10.0 mass% / (cm 3 / g) or less, and more preferably 1.0 mass % / (cm 3 / g) or more and 8.0 mass% / (cm 3 / g) or less.
[0047] The average thickness T (nm) is the average value of the thickness of the covering portion in the particles of each active material. The average thickness T (nm) can be measured, for example, by a scanning transmission electron microscope (STEM). In addition, it can also be analyzed and measured in combination with energy dispersive X-ray analysis (EDS) as needed. Specifically, a line analysis can be performed on the surface of the active material, and based on the result, the peak width of the A element is measured as the thickness of the covering portion. It should be noted that the line analysis can be performed in the same manner as the determination of the half-peak width described later. In addition, the average thickness T (nm) can be set to the average value when 10 places on the surface of the active material are measured by the above method.
[0048] The amount W (mass %) of the element A is the average amount of the element A in each active material particle. The amount W (mass %) of the element A is determined by measuring the amount of the element A by ICP emission spectrometry and subtracting the amount of the element A in the core.
[0049] The specific surface area S (m 2 The specific surface area S (m 2 / g) By using a flowing gas adsorption method specific surface area measuring device, nitrogen gas was circulated at a gas volume of 30 mL / min while replacing the inside of the glass colorimetric cell for 5 minutes, and then pretreated at 250°C for 10 minutes in a nitrogen atmosphere, and then measured by the BET 1-point method.
[0050] From the perspective that the function of the active material as the core is not easily hindered by the covering part and the performance of the core as the active material can be fully exerted, the average thickness T of the covering part is preferably 50 nm or less. From the perspective of making this advantage more significant, the average thickness T of the covering part is more preferably 40 nm or less, further preferably 35 nm or less, and further preferably 30 nm or less, 25 nm or less.
[0051] On the other hand, when the average thickness T of the covering portion is 0.1 nm or more, it is possible to effectively prevent the performance of the active material from being reduced, and thus it is preferred. From the perspective of making this advantage more significant, the average thickness T of the covering portion is more preferably 1.0 nm or more, further preferably 3.0 nm or more, and further preferably 5.0 nm.
[0052] From the perspective of not hindering the capacity and rate characteristics of the core, the amount W of the A element is preferably 0.001 mass % or more and 2.000 mass % or less. From the perspective of making this advantage more significant, the amount W of the A element is more preferably 0.01 mass % or more and 1.0 mass % or less, and further preferably 0.01 mass % or more and 0.5 mass % or less.
[0053] From the perspective of improving the capacity and rate characteristics of the core, the specific surface area S is 0.1m 2 / g or more and 2.0m 2 From the perspective of making this advantage more significant, the specific surface area S is more preferably 0.2 m 2 / g or more, more preferably 0.3m 2 On the other hand, the specific surface area S is more preferably 1.5 m 2 / g or less, more preferably 1.0 m 2 / g or less.
[0054] As described above, the coating in the active material of the present invention preferably covers the surface of the core as thinly and densely as possible, and this coating state can be evaluated by a spectrum obtained by line analysis from the surface to the inside of the active material by the STEM method at the cross section of the active material.
[0055] Specifically, the half-width of the peak of the A element in the spectrum is related to the thickness and density of the covering portion, and from the perspective that the covering portion can effectively prevent the performance of the core portion from being reduced without weakening the performance of the core portion, it is preferred that the half-width is 25 nm or less. From this perspective, the half-width is more preferably 20 nm or less, and further preferably 16 nm or less.
[0056] From the perspective of effectively preventing the performance of the core from being degraded by the covering portion, the half-width is preferably 0.005 nm or more, more preferably 0.05 nm or more, further preferably 0.5 nm or more, further preferably 3.0 nm or more, further preferably 5.0 nm or more.
[0057] When two or more A elements are contained in the coating portion, the half-value width of at least one of the A elements may be less than or equal to the above value, and the half-value widths of all the A elements are preferably less than or equal to the above value.
[0058] The half peak width is measured by the following method.
[0059] The average intensity distribution of the A element in the coating portion was measured using an energy dispersive X-ray analyzer (EDS). The measurement conditions by EDS are as follows.
[0060] The powder of the active material is embedded in resin, and a thin slice sample that can be observed by TEM is prepared using a focused ion beam. A scanning transmission electron microscope (STEM) mounted on an EDS is used to observe the vicinity of the surface of the active material, and the region including the coating is taken as the object, and the mapping data of the A element is obtained by EDS. Based on the obtained element mapping data, the average intensity line distribution of the A element as a component of the coating is extracted. The device used in this measurement is as follows.
[0061] STEM: JEM-ARM200F (manufactured by JEOL Ltd.)
[0062] EDS: JED-2300T DRY SD100GV (manufactured by JEOL Ltd.)
[0063] EDS analysis software: NSS Ver4.1 (manufactured by Thermo Fisher Scientific)
[0064] Conditions for obtaining element mapping data
[0065] Acceleration voltage: 200 kV, magnification: 2 million times, STEM image acquisition detector: ADF
[0066] STEM image acquisition resolution: 512×512 pixels, EDS mapping resolution: 256×256 pixels (appropriately adjust the magnification and measurement time to obtain the mapping data of the A element of the cover.)
[0067] · Average intensity distribution acquisition content
[0068] For element A, based on the obtained element mapping data, the line distribution (100 points) of the net intensity obtained by removing the background from the area (about 70 to 90 nm) in the vertical direction containing the active material and the entire covering layer is extracted with a width of about 50 nm in the horizontal direction relative to the flat active material surface.
[0069] The covering portion only needs to exist in a manner that covers the surface of the core portion. Therefore, the covering portion may cover the entire surface of the core portion, or may cover a portion of the surface of the core portion. The coverage of the covering portion relative to the entire surface of the core portion is, for example, preferably 60% or more, more preferably 70% or more, particularly preferably 80% or more, and further preferably 90% or more. The coverage of the covering portion can be confirmed by, for example, a method of combining a scanning transmission electron microscope (STEM) and energy dispersive X-ray analysis (EDS) as required to observe the surface of the active material, or by Auger electron spectroscopy.
[0070] [Active substance]
[0071] The shape of the active material of the present invention is not particularly limited, and examples thereof include granular shapes. The size of the particles of the active material of the present invention is determined by the cumulative volume diameter D at 50% by volume obtained by laser diffraction scattering particle size distribution measurement. 50 (hereinafter, also referred to as "average particle size") indicates, for example, preferably 0.5 μm or more, preferably 1.0 μm or more, preferably 2.0 μm or more, preferably 2.5 μm or more. This is because excessive aggregation between particles can be suppressed, and dispersibility will be improved. On the other hand, the volume cumulative particle size D 50 For example, it is preferably 20.0 μm or less, more preferably 15.0 μm or less, and particularly preferably 10.0 μm or less. This is because the contact between the active material particles and the contact between the active material particles and the solid electrolyte particles can be sufficiently ensured.
[0072] Here, the volume cumulative particle size D 50 A substitute value representing the average particle size of particles including primary particles and secondary particles. "Primary particles" refer to the smallest unit of particles surrounded by grain boundaries when observed by SEM (scanning electron microscope, e.g., 500 to 5000 times). Unless otherwise specified, the active material of the present invention refers to primary particles. On the other hand, in the present invention, "secondary particles" refer to particles in which multiple primary particles are aggregated in a manner that shares a portion of their respective peripheries (grain boundaries) and are independent of other particles.
[0073] Volume cumulative particle size D 50The measurement was performed by the following method. Using an automatic sampler for a laser diffraction particle size distribution measuring device (Microtrac SDC manufactured by Microtrac BEL), the powder of the active material was added to a solvent in which 0.1% by mass of hexametaphosphoric acid was mixed in a 20% by mass ethanol solvent, and 40W ultrasonic waves were irradiated at a flow rate of 40% for 90 seconds. The particle size distribution was measured using a laser diffraction particle size distribution measuring device "MT3000II" manufactured by Microtrac BEL, and the volume cumulative particle size D was measured based on the obtained volume-based particle size distribution graph. 50 .
[0074] Make determination D 50 The water-soluble solvent was passed through a 60 μm filter, the “solvent refractive index” was set to 1.33, the particle permeability condition was set to “permeation”, the measurement range was set to 0.243 μm or more and 704.0 μm or less, the measurement time was set to 30 seconds, and the average value of the two measurements was taken as D 50 .
[0075] From the perspective of reducing the interface resistance between the active material and the solid electrolyte, it is advantageous to adjust the water content of the active material of the present invention to a certain range. Specifically, if the water content of the active material is too high, the interface resistance between the active material and the solid electrolyte may increase.
[0076] The water content (mass ppm) of the active material of the present invention at 300°C measured by the Karl Fischer method may be, for example, less than 600 ppm, less than 550 ppm, or less than 500 ppm. In addition, the water content may be more than 10 ppm, more than 50 ppm, more than 100 ppm, or more than 200 ppm. From the perspective of reducing the structural degradation of the active material caused by the reaction with lithium and reducing the reaction with the electrolyte during battery operation, the less the amount of water contained in the active material, the better. In order to minimize the amount of water contained in the active material, the active material may be dried at a temperature of, for example, 300°C, under vacuum or in an inactive atmosphere.
[0077] The procedure for measuring the moisture content by the Karl Fischer method is as follows. That is, using a Karl Fischer moisture meter, the test sample is heated to 110°C and the released moisture content (mass ppm) is measured. Then, the test sample is heated to 300°C and the released moisture content (mass ppm) is measured. The value obtained by adding the two values is used as the moisture content. The measurement is performed in a nitrogen atmosphere, and a measurement device such as CA-100 (manufactured by Mitsubishi Chemical Corporation) is used.
[0078] [Method for producing active substance]
[0079] Next, a preferred method for producing the active material of the present invention is described. In this production method, after forming the core portion by a conventional method, the covering portion is formed by atomic layer deposition (hereinafter also referred to as "ALD").
[0080] The manufacturing method of the core is not particularly limited, and a composite oxide containing lithium (Li) element, manganese (Mn) element and oxygen (O) element can be manufactured by a known method. For example, lithium carbonate powder and manganese oxide powder (e.g., manganese dioxide powder) are used as raw materials, mixed to obtain a mixed powder, and the mixed powder is calcined to obtain a composite oxide. The composite oxide thus obtained is crushed and adjusted to a desired particle size to obtain the core.
[0081] On the surface of the core thus obtained, a covering portion is formed by ALD. Since the covering portion can be formed atomically layer by atomic layer by ALD in theory, a thin and dense covering portion can be formed. For example, a sol-gel method can be considered as another method for forming a covering portion, but it is not easy to form a thin and dense covering portion by a sol-gel method.
[0082] When forming a covering portion containing aluminum and oxygen, for example, the covering portion can be formed in the following manner. The covering portion can be formed by a method having the following steps, namely, first, a first step of placing a core portion in a reaction chamber; a second step of heating the reaction chamber to remove moisture attached to the core portion; a third step of heating the reaction chamber to a film forming temperature and adding a precursor substance of the covering portion; a fourth step of adding an oxidant to the chamber; a fifth step of removing excess precursor substances and reaction products in a gas phase; and a sixth step of adding an oxidant to the chamber.
[0083] In the first step, an inert gas is preferably introduced into the reaction chamber to form a fluidized bed. As the inert gas, nitrogen or argon can be used, for example. The flow rate of the inert gas (N2, Ar) can be set at, for example, 10 cm 3 / min to 100 L / min.
[0084] The heating temperature in the second step can be set, for example, in the range of 100° C. to 200° C. In addition, the heating time at this time can be set, for example, in the range of 1 hour to 12 hours.
[0085] The heating temperature in the third step is not particularly limited as long as it is a temperature at which the covering portion can be formed into a film, and can be set, for example, in the range of 50°C to 400°C. Examples of the precursor substance include organic aluminum compounds such as trimethylaluminum (hereinafter also referred to as "TMA"). In addition, in the third step, the heated precursor substance can also be added to the reaction chamber. The temperature for heating the precursor substance can be, for example, above room temperature and below 300°C. It should be noted that the third step is preferably carried out until the precursor substance is chemically adsorbed on the surface of the core portion to form a single phase.
[0086] Examples of the oxidizing agent used in the fourth step include H 2 O, O 3 , H 2 O 2 , H 2 plasma, O 2 plasma, Ar plasma, and N 2 O plasma.
[0087] In the fifth step, for example, excess precursor substances and reaction products can be removed by purging. Examples of the reaction product include methane gas.
[0088] In the sixth step, the core is exposed to an oxidant to react with the precursor material in a single phase, and the target covering portion can be formed by the reaction. As the oxidant, the same oxidant as that used in the fourth step can be used.
[0089] By repeating the operations of the first step to the sixth step until the target film thickness is obtained, a thin and dense covering portion can be smoothly formed.
[0090] It is preferable to repeat the first step to the sixth step so that the amount of the A element contained in the coating portion falls within a range of, for example, 10 ppm to 50000 ppm.
[0091] As the precursor used in the present invention, for example, when the A element is Zr, Zr(NEtMe)4, ZrI4, ZrCp2Me2, ZrCp2Me2, ZrCp2Me(OMe), ZrCp2Cl2, ZrCp(NMe2)3, ZrCl4, Zr[N(SiMe3)2]2Cl2, Zr(thd)4, Zr(NEt2)4, Zr(O t Bu)4、Zr(O t Bu)2(dmae)2、Zr(O i Pr)4、Zr(O i Pr)2(dmae)2, Zr(NEtMe)4, Zr(NEtMe)3(guan-NEtMe), Zr(NEtMe)2(guan-NEtMe)2, Zr(MeCp)(TMEA), ZrTDMA, Zr(MeAMD)4, Zr(dmae)4, Zr(CpMe2)2Me(O tBu), Zr(CpMe)CHT, Zr(CpMe)2Me2, Zr(Cp2CMe2)Me(OMe), Zr(Cp)( t BuDAD)(O i Pr).
[0092] For example, when the element A is Al, AlMe3, AlMe2O i Pr, AlMe2H, AlMe2Cl, AlMe2(C3H6NMe2), AlH3N: (C5H 11 ), AlEt3, AlCl3, AlBu3, Al2(NMe2)6, Al(O s Bu)3、Al(O n Pr)3, Al(OEt)3, Al(NMe2)3, Al(N i Pr2)3、Al(N i Pr2)2(C3H6NMe2), Al(NEt2)3, Al(NEt2)2(C3H6NMe2), Al(mmp)3, Al( i PrAMD)Et2,Al(CH3)3.
[0093] For example, when the A element is Ti, Tb(thd)3, Ti(Cp)CHT, Ti(CpMe)(O i Pr)3, Ti(CpMe5)(OMe)3, Ti(EtCp)(NMe2)3, Ti(NEt2)4, Ti(NEtMe)3(guan-NEtMe), Ti(NEtMe)4, Ti(N Me2)3(CpMe), Ti(NMe2)3(CpN), Ti(NMe2)3(dmap), Ti(NMe2)4, Ti(NMeEt)4, Ti(Np)4, Ti(OEt)4, Ti(O i Pr)2(dmae)2、Ti(O i Pr)2(NMe2)2、Ti(O i Pr)2(thd)2、Ti(O i Pr)3( i Pr2AMD)、Ti(O i Pr)4、Ti(OMe)4、Ti(O t Bu)4, TiCl4, TiCp2(( i PrN)2C(NH i Pr)), TiF4, TiI4.
[0094] For example, when the element A is Ta, Ta(NEt)(NEt2)3, Ta(NEt2)3N t Bu, Ta(NEt2)5, Ta(NEtMe)2(N i Pr)、Ta(NEtMe)5、Ta(N i Pr)(NEtMe)2, Ta(NMe2)3(CMe2Et), Ta(NMe2)5, Ta(N t Am)(NMe2)3、Ta(N t Am)[(NMe2)]3、Ta(N t Bu)( i PrAMD)2(NMe2), Ta(N t Bu)(NEt2)3、Ta(N t Bu)( t Bu2pz)3, Ta(OEt)4(dmae), Ta(OEt)5, TaBr5, TaCl5, TaCp(N t Bu)(NEt2)2, TaF5, TaNp3Cl2.
[0095] For example, when the A element is Nb, Nb(N t Bu)(NEt2)3, Nb(N t Bu)(NEtMe)3, Nb(OEt)5, NbCl5, NbF5.
[0096] When the coating portion contains lithium in addition to the A element and the oxygen element, a precursor substance containing Li may be used in the ALD. Examples of the precursor containing Li include LiO t Bu, LiOSiMe3, LiN(SiMe3)2, Li(thd), Li(N(SiMe3)2), etc.
[0097] 〔Electrode mixture〕
[0098] The active material of the present invention thus obtained can be used in the form of an electrode mixture containing, for example, the active material and an electrolyte. The electrolyte can be any one of a solid and a liquid. When a solid electrolyte is used as an electrolyte, when the total solid component is set to 100% by mass, the content of the active material of the electrode mixture can be more than 30% by mass, can be more than 40% by mass, or can be more than 50% by mass. In addition, the content of the above-mentioned active material can be, for example, less than 98% by mass, can be less than 90% by mass, or can be less than 85% by mass. By making the content of the active material the aforementioned range, the function as an electrode can be fully exerted.
[0099] The solid electrolyte that can be used in the present invention may be the same as the solid electrolyte used in a conventional solid-state battery. For example, sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, halide solid electrolytes, etc. may be listed, among which sulfide solid electrolytes are preferred. The sulfide solid electrolyte may be, for example, a solid electrolyte containing lithium (Li) elements and sulfur (S) elements and having lithium ion conductivity, or a solid electrolyte containing lithium (Li) elements, phosphorus (P) elements, and sulfur (S) elements and having lithium ion conductivity. The sulfide solid electrolyte may be any one of a crystalline material, glass ceramics, and glass. The sulfide solid electrolyte may have a crystalline phase of an argyrodite-type structure. As such a sulfide solid electrolyte, for example, Li2S-P2S5, Li2S-P2S5-LiX (wherein "X" represents one or more halogen elements), Li2S-P2S5-P2O5, Li2S-Li3PO4-P2S5, Li3PS4, Li4P2S6, Li 10 GeP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4、Li7P3S 11 , Li 3.25 P 0.95 S4, Li a PS b X c (wherein X is at least one halogen element. a represents a number greater than or equal to 3.0 and less than or equal to 6.0. b represents a number greater than or equal to 3.5 and less than or equal to 4.8. c represents a number greater than or equal to 0.1 and less than or equal to 3.0.) In addition, sulfide solid electrolytes described in, for example, WO2013 / 099834A1 and WO2015 / 001818A1 can also be cited.
[0100] The electrolyte that can be used in the present invention can be the same as the electrolyte used in a conventional liquid battery. For example, an organic electrolyte, a polymer solid electrolyte, a molten salt, etc. can be used. As an organic electrolyte, for example, as a solvent, esters such as propylene carbonate, ethylene carbonate (hereinafter referred to as EC), butylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, γ-butyrolactone (hereinafter referred to as GBL) can be listed; substituted tetrahydrofurans such as tetrahydrofuran and 2-methyltetrahydrofuran; ethers such as dioxolane, ethyl ether, dimethoxyethane, diethoxyethane, methoxyethoxyethane; dimethyl sulfoxide, cyclopentane, methyl cyclopentane, acetonitrile, methyl formate, methyl acetate, etc., and one or more mixed solvents of these can be listed. In addition, examples of electrolyte salts dissolved in an organic solvent include lithium perchlorate, lithium borofluoride, lithium hexafluorophosphate (hereinafter referred to as "LiPF6"), lithium hexafluoroarsenate, lithium trifluoromethanesulfonate, lithium halides, lithium aluminum chloride and other lithium salts.
[0101] The active material contained in the electrode mixture can be only the active material of the present invention, or can be a combination of the active material of the present invention and other active materials. As other active materials, particles consisting of known lithium transition metal composite oxides can be listed. When the active material of the present invention and other active materials are used in combination, relative to the active material as a whole, the active material of the present invention preferably contains more than 50% by mass, and particularly preferably contains more than 70% by mass.
[0102] When the electrode mixture contains a solid electrolyte, the electrode mixture may contain other materials such as a conductive additive and a binder as needed. The electrode mixture is mixed with a solvent to make a paste, and the paste is applied to a current collector such as an aluminum foil and dried to make an electrode layer such as a positive electrode layer. In addition, in the case of a powder pressed battery rather than a coated battery, the electrode layer can be made by mixing the materials of the active material, solid electrolyte, and conductive additive in a solid phase and molding them into particles.
[0103] 〔Battery〕
[0104] The active material of the present invention can be suitably used as a positive electrode active material of a battery. The battery can be a primary battery or a secondary battery. The battery of the present invention can be, for example, a battery having a positive electrode layer, a negative electrode layer, and an electrolyte layer disposed between the positive electrode layer and the negative electrode layer and containing an electrolyte solution. The positive electrode layer contains the active material of the present invention.
[0105] The active material of the present invention can be suitably used as a solid-state battery, especially a solid-state lithium battery. Among them, it can be suitably used as a secondary battery, especially a solid-state lithium secondary battery. As the shape of the battery, for example, a laminated type, a cylindrical type, a square type, and a coin type can be listed.
[0106] Preferably, the solid-state battery has a positive electrode layer, a negative electrode layer, and a solid electrolyte layer located therebetween, and the positive electrode layer comprises the active material of the present invention described above. The solid-state battery can be made, for example, by sequentially stacking the positive electrode layer, the solid electrolyte layer, and the negative electrode layer and press-molding. In addition to solid-state batteries that do not contain any liquid or gel-like substances as electrolytes, "solid-state batteries" also include forms containing, for example, less than 50% by mass, less than 30% by mass, or less than 10% by mass of liquid or gel-like substances as electrolytes.
[0107] The negative electrode active material used for the negative electrode layer can be the same as the negative electrode active material used in conventional solid-state batteries. As a specific negative electrode active material, materials for embedding / de-embedding lithium ions can be used, such as carbon materials, silicon, Si-O and other silicon oxide compounds, tin compounds, lithium titanate and other well-known materials. As the carbon material, for example, materials obtained by sintering organic polymer compounds such as polyacrylonitrile, phenolic resin, phenol novolac resin, cellulose, artificial graphite, and natural graphite can be listed. In addition to using such a negative electrode active material, the negative electrode layer can also be made in the same way as the positive electrode layer.
[0108] Example
[0109] Hereinafter, the present invention will be described in more detail by way of examples, but the scope of the present invention is not limited to these examples.
[0110] [Example 1]
[0111] (1) Preparation of the core
[0112] A spinel lithium-manganese-nickel composite oxide (hereinafter, also referred to as "LMNO") was prepared as a core. As a result of chemical analysis, LMNO contained 4.1 mass % Li, 41.7 mass % Mn, 13.3 mass % Ni, and 5.3 mass % Ti.
[0113] (2) Formation of Covering Part
[0114] A coating containing element A and oxygen was formed on the surface of the core by ALD. The elements shown in Table 1 below were used as element A. Tris(dimethylamino)cyclopentadienyl zirconium (ZrCp(NMe2)3) was used as a precursor containing element A. Nitrogen was used as an inert gas at a rate of 50 cm 3 A fluidized bed was formed in the reaction chamber at a flow rate of 1 / min. Then, the film forming temperature in the reaction chamber was set to 350°C, precursor materials were introduced, and water was used as an oxidant to form a film in a manner such that the Zr content reached 150 ppm. Thus, the target active material was obtained.
[0115] [Examples 2 and 3]
[0116] An active material was obtained in the same manner as in Example 1 except that the amount of Zr in Example 1 was changed to 600 ppm (Example 2) or 900 ppm (Example 3).
[0117] [Example 4]
[0118] An active material was obtained in the same manner as in Example 1 except that the precursor material in Example 1 was changed to tetrakis(dimethylamino)zirconium (ZrTDMA) and the amount of Zr was changed to 1500 ppm.
[0119] [Comparative Example 1]
[0120] No covering portion was formed in Example 1. Except for this, the same procedure as in Example 1 was carried out to obtain an active material.
[0121] 〔evaluate〕
[0122] The average thickness T of the coating, the specific surface area S of the active material, and the amount W of the A element were measured by the above method for the active materials obtained in the examples and comparative examples. In addition, the half-peak width of the spectrum obtained by line analysis based on the STEM method was measured. Furthermore, the particle size D was measured by the above method. 50 Furthermore, the rate characteristics and cycle characteristics of the battery containing the active material were measured by the following method. These results are shown in the following Table 1.
[0123] 〔Battery Assembly〕
[0124] Weigh 8.0 g of the powder of the active material obtained in the examples and comparative examples and 1.0 g of acetylene black (manufactured by Denki Kagaku Kogyo Co., Ltd.), and mix them in a mortar for 10 minutes. Then, add the mixture of the powder of the active material and acetylene black to a solution obtained by dissolving 12% by mass of PVdF (manufactured by KISHIDA CHEMICAL Co., Ltd.) in 8.3 g of N-methylpyrrolidone (NMP), and further mix. Then, add 5 mL of NMP and mix thoroughly to prepare a paste. Apply the paste on aluminum foil as a current collector. The paste is applied using a coating machine with a gap adjusted to 100 μm to 280 μm. The coating of the paste is vacuum dried at 140°C for one day and one night. Then, the linear pressure is 0.3 t / cm 2 The aluminum foil was punched into a circular shape with a diameter of 16 mm and used as a positive electrode.
[0125] Immediately before making the battery, the positive electrode was vacuum dried at 200°C for more than 300 minutes to remove the attached moisture, and then assembled into the battery. In addition, the average mass of the aluminum foil with a diameter of 16 mm was calculated in advance, and the mass of the aluminum foil was subtracted from the mass of the positive electrode to calculate the mass of the positive electrode mixture. In addition, the content of the active material was calculated based on the mixing ratio of the active material, acetylene black and PVdF.
[0126] As the negative electrode, a metal Li foil with a diameter of 19 mm and a thickness of 0.5 mm was used. As the electrolyte, a solvent obtained by mixing ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7 was used as a solvent, and on this basis, a substance in which 1 mol / L of LiPF6 was dissolved was used as a solute.
[0127] A battery for electrochemical evaluation was prepared using the above-mentioned positive electrode, negative electrode and electrolyte.
[0128] 〔Initial activity〕
[0129] The prepared battery was activated by the following method: After charging to 4.999 V at 0.1C constant current and constant potential at 25°C, the battery was discharged to 3.0 V at 0.1C constant current. This cycle was repeated three times. It should be noted that the actual current value was calculated based on the content of the positive electrode active material in the positive electrode.
[0130] 〔Rate characteristics〕
[0131] The battery after initial activity activation as described above was charged to 4.999 V at 0.1C constant current and constant potential at 25°C. After charging, it was discharged to 3 V at 1C constant current. The value obtained by dividing the discharge capacity at 5C constant current to 3 V by the discharge capacity at 0.1C to 3 V was used as an index of rate characteristics.
[0132] 〔Cycling Characteristics〕
[0133] Separately, the battery after initial activation was charged and discharged at 0.1C constant current and constant potential in the charge and discharge range of 3.0 to 4.999 V at 25°C, then discharged at 0.1C constant current for one cycle, and then charged and discharged at 0.5C for 50 cycles.
[0134] The percentage (%) of the value obtained by dividing the discharge capacity at the 50th cycle by the discharge capacity at the 2nd cycle was taken as the value of the cycle characteristic.
[0135] [Table 1]
[0136]
[0137] The results shown in Table 1 show that the active materials obtained in each example have better rate characteristics than the active materials of the comparative examples. This is believed to be because the interface resistance on the surface of the active materials obtained in each example is low.
[0138] In addition, it is found that the active material obtained in each example has better cycle characteristics than the active material of the comparative example. This is probably because the active material obtained in each example suppresses the dissolution of manganese during the charge and discharge process of the battery.
[0139] Industrial Applicability
[0140] According to the present invention, an active material capable of obtaining excellent battery performance and a method for producing the same can be provided.
Claims
1. An active material comprising a core portion and a coating portion located on a surface of the core portion, The core contains lithium (Li), manganese (Mn) and oxygen (O). The covering portion includes an A element (A is at least one selected from the group consisting of Ti, Zr, Ta, Nb and Al) and an oxygen (O) element. The average thickness of the coating is T (nm), the specific surface area of the active material is S (nm 2 / g), when the amount of the A element contained in the coating is W (mass %), the value of W / (S×T) is greater than 0 and is 15 mass % / (cm 3 / g) or less.
2. An active material comprising a core portion and a coating portion located on a surface of the core portion, The core contains lithium (Li), manganese (Mn) and oxygen (O). The covering portion includes an A element (A is at least one of Ti, Zr, Ta, Nb and Al) and an oxygen (O) element. In a spectrum obtained by line analysis from the surface to the inside of the active material by a STEM method at a cross section of the active material, a half-value width of a peak of the A element in the spectrum is 25 nm or less.
3. The active material according to claim 1 or 2, wherein The core portion contains a spinel-type composite oxide including a lithium (Li) element, a manganese (Mn) element, and an oxygen (O) element.
4. The active material according to any one of claims 1 to 3, wherein The covering portion further contains lithium (Li) element.
5. The active material according to any one of claims 1 to 4, wherein The average thickness T of the covering portion is 50 nm or less.
6. The active material according to any one of claims 1 to 5, wherein The specific surface area S is 0.1 m 2 / g or more and 2.0m 2 / g or less. 7 . The active material according to claim 1 , which has a water content of 600 ppm or less. 8 . The active material according to claim 1 , which has an average particle size of 0.5 μm or more and 20 μm or less. 9 . An electrode mixture comprising the active material according to claim 1 and an electrolyte. 10 . An electrode mixture comprising the active material according to claim 1 and a solid electrolyte.
11. The electrode mixture according to claim 9 or 10, wherein When the total solid content is 100 mass %, the content of the active material is 30 mass % or more and 98 mass % or less. 12 . A battery comprising a positive electrode layer, a negative electrode layer, and an electrolyte layer, wherein the electrolyte layer is disposed between the positive electrode layer and the negative electrode layer and contains an electrolytic solution, and the positive electrode layer contains the active material according to claim 1 . 13 . A battery comprising a positive electrode layer, a negative electrode layer, and an electrolyte layer, wherein the electrolyte layer is disposed between the positive electrode layer and the negative electrode layer and contains a solid electrolyte, and the positive electrode layer contains the active material according to claim 1 .
14. A method for producing an active material according to any one of claims 1 to 8, wherein: On the surface of the core containing lithium (Li) element, manganese (Mn) element and oxygen (O) element, a covering part containing A element (A is at least one of Ti, Zr, Ta, Nb and Al) and oxygen (O) element is formed by atomic layer deposition.
